Corporate Finance and Firm Value in The Indonesian Manufacturing Companies - Handriani, Eka; Robiyanto, Robiyanto (International Research Journal of Business Studies, 2018)
This study examines the impact of dividend policy, investment decision, and funding policy on firm value in the Indonesian manufacturing companies. This study was conducted by using 178 manufacturing companies listed in the Indonesia Stock Exchange (IDX) during the period 2009 - 2016. Samples were taken by using a purposive sampling method. This study aims to examine the firm value’s main determinants of the manufacturing companies in Indonesia based on basic theory of capital structure through building theoretical model. Partial Least Square through path analysis was used to analyze the data. The findings shows that dividend policy, investment decision, and funding policy have a positive impact on the Indonesian manufacturing companies’ firm value. This study supports the theory of pecking order and agency theory.